Case Report: A Challenging Localization of a Pulmonary Ectopic ACTH-Secreting Tumor in a Patient With Severe Cushing’s Syndrome - Serban, Andreea Liliana; Rosso, Lorenzo; Mendogni, Paolo; Cremaschi, Arianna; Indirli, Rita; Mantovani, Beatrice; Rumi, Mariagrazia; Castellani, Massimo; Chiti, Arturo; Croci, Giorgio Alberto; Mantovani, Giovanna; Nosotti, Mario; et al. (Frontiers in Endocrinology, 2021)
Background: Ectopic adrenocorticotropic syndrome (EAS) is a rare cause of endogenous ACTH-dependent Cushing’s Syndrome, usually associated with severe hypercortisolism as well as comorbidities. Tumour detection is still a challenge and often requires several imaging procedures. In this report, we describe a case of an ectopic ACTH secretion with a misleading localization of the responsible tumour due to a concomitant rectal carcinoma. Case presentation: A 49-year-old man was referred to our Endocrinology due to suspicion of Cushing’s Syndrome. His medical history included metastatic rectal adenocarcinoma, diagnosed 5 years ago and treated with adjuvant chemotherapy, radiotherapy and surgical resection. During follow-up, a thoracic computed tomography scan revealed two pulmonary nodules located in the superior and middle lobes of the right lung with a diameter of 5 and 10 mm, respectively. However, these nodules remained radiologically stable thereafter and were not considered relevant. All biochemical tests were suggestive of EAS (basal ACTH levels: 88.2 ng/L, nv 0-46; basal cortisol levels: 44.2 µg/dl, nv 4.8-19.5; negative response to CRH test and high dose dexamethasone suppression test) and radiological localization of the ectopic ACTH-secreting tumour was scheduled. The CT scan revealed a dimensional increase of the right superior lung nodule (from 5 to 12 mm). [68Ga]-DOTA-TOC PET/CT scan was negative, while [18F]-FDG-PET/CT showed a tracer accumulation in the superior nodule. After multidisciplinary consultation, the patient underwent thoracic surgery that started with two atypical wedge resections of nodules. Frozen section analyses showed a neuroendocrine tumour on right middle lobe nodule and a metastatic colorectal adenocarcinoma on the superior lesion. Then, right superior nodulectomy and right middle lobectomy with mediastinal lymphadenectomy was performed. The final histopathological examination confirmed a typical carcinoid tumour, strongly positive for ACTH. Post-surgical follow-up showed a persistent remission of Cushing’s syndrome. Conclusions: The present report describes a case of severe hypercortisolism due to EAS not detected by functional imaging methods, in which the localization of ACTH ectopic origin was puzzled by a concomitant metastatic rectal carcinoma. The multidisciplinary approach was crucial for the management of this rare disease.